National train-the-trainer certificate programme for improving healthcare communication in Austria. Issue 12 (December 2021) - Sator, Marlene; Holler, Peter; Rosenbaum, Marcy
Abstract: Objectives: In Austria a national train-the-trainer programme (TTT) has been developed, implemented and evaluated with the aim of training and certifying participants for developing, implementing and delivering communication skills training (CST) for health professionals. Methods: The programme included 5 in-person courses, application homework with feedback, peer work, and regular trainer network meetings. Global satisfaction with training and changes in self-efficacy among TTT-participants and their learners in the CST delivered as practice projects were evaluated. Results: 18 participants have graduated from the TTT-pilot. 98 people took part in the 9 CST delivered by TTT-participants. Participants' satisfaction has been rated very positively both for TTT and CST. At post-programme/post-training, statistically significant improvement was observed in self-efficacy for the TTT-participants and for the CST-participants. Additionally, valuable suggestions for programme/training improvement were identified. Conclusions: This programme is an important step to sustainably improving CST in Austria. To guarantee high quality and consistency, a set of standards for certification have been developed for TTT and CST. Practice implications: Implementation of best practices in training trainers and communication skills teaching can be guided by a structured approach. Those wanting to implement similar programmes can benefit from strengths and suggestions for improvement identified in this national project. Highlights: In Austria, a national programme for improving healthcare communication was piloted. Large-scale communication skills programmes can be guided by a structured approach. The train-the-trainer approach used effectively improved participants' skills. Quality standards will guarantee high quality and consistency of the programme. Lessons learned can contribute to others interested in implementing such programmes.